Political Participation and Women in India: Examining the Role of Political Support in Achieving Gender Equity (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Democracy infers uniformity for every human individual, people. As against this essential idea of democracy what is ordinarily observed is that ladies are prohibited from various different backgrounds, all the more unmistakably in Politics. The U.N. sees that females comprise world's biggest prohibited classification. For the accomplishment of genuine fair sprit will be guaranteed better political support. In the battle for sex equity, Usha Narayanan contends, political support establishes the as a matter of first importance step toward that path.